A Novel Semi-fragile Watermarking Algorithm for 3D Mesh Models - Xu Tao; Cai Zhao-quan (2012 International Conference on Control Engineering and Communication Technology, 2012)
A novel semi-fragile watermarking algorithm based on mesh content was proposed. 3D mesh models were calibrated by principal component analysis first, and then this algorithm constructed spherical coordinates mapping square-matrix to realize 2D parameterization of vertex's geometric data. A binary image was chosen as the semi-fragile watermark and hidden in coefficients of square-matrix. Experimental results show that the proposed algorithm can tolerate various mesh normal processing, such as mesh translation, mesh rotation, mesh uniformed scaling, while is sensitive to malicious tampering, such as vertex random noising.